Future market segments for hybrid maize in East Africa - Rutsaert, Pieter; Donovan, Jason A.; Mawia, Harriet; Sousa, Kauê de; Etten, Jacob van (CGIAR System Organization, 2022)
The current seed product market segmentation by the Consultative Group on International Agricultural Research (CGIAR) for maize in East Africa includes four segments, which differ by agro-ecological zone and maturity class. However, considering the lengthy period required to produce a variety, from initial design to commercial production, a critical question should be asked: what are future segments that should be considered in discussions on current breeding investments? Video-based product concept testing (VPCT) is a novel approach for gathering insights from farmers about their varietal preferences to inform future market segmentation. This brief explains the conceptual and methodological underpinnings of VPCT. We present an application of the tool in hybrid maize. Seven new product concepts (representing potential future market segments) were identified based on discussions with breeders, seed companies and farmers, which we labelled: home use, intercropping, drought avoidance, nutritious, feed (yellow), green maize and food and fodder. These future concepts, together with the resilient benchmark product concept (the current breeding target), were evaluated through triadic comparisons with 2400 farmers in Kenya and Uganda. In Uganda, the drought avoidance concept ranked high, while in Kenya the intercropping concept stood out. Concept testing provides a strong case for new investments to integrate agronomic practices and preferences of farmers into breeding, on-farm testing and seed systems. Future work will estimate the implications of increased availability (and uptake) of these future segments on the current segmentation.